No hero the evolution of a Navy SEAL - Owen, Mark 1976?-; Maurer, Kevin
Recounts definitive moments from the authors career as a Navy SEAL, discussing the missions that had the greatest personal meaning for him and explaining the lessons and values he hopes to pass on to the next generation.